Produktivitas Pengelolaan Tanah Wakaf Di Desa Munggu Kecamatan Bungkal Kabupaten Ponorogo Perspektif Hukum Wakaf Di Indonesia - Shokhifah, Eka Zhahrotu; Wahyudi, Wahyudi (Journal of Sharia Economic Law, 2024)
The background to this research is that the productivity of waqf land in Munggu Village, Bungkal District, is no longer productive due to a lack of Human Resources (HR) and Nadzir's lack of insight to manage it. This thesis reports the results of research with problem formulation (1) What is the productivity of waqf land management in Munggu Village, Bungkal District, Ponorogo Regency? (2) What is the productivity of waqf land management in Munggu Village, Bungkal District, Ponorogo Regency from the perspective of waqf law in Indonesia? This research was conducted using a qualitative research approach and a case study type with data collection procedures through interview, observation and documentation techniques. Meanwhile, for data analysis techniques, the author uses Data Reduction (Data Redaction), Data Display (Data Presentation), Data Verification (Conclusion Drawing Process) Based on the results of data analysis, it is concluded that (1) the productivity of waqf land in Munggu Village has been managed and operationalized into two institutions, namely the Institute (TPQ) and the TK institution, the lack of Human Resources (HR) and Nadzir's lack of insight are the main causes of the institution (2) In terms of managing and developing the productivity of waqf land, it is not in accordance with the Waqf Law in Indonesia, because Article 5, Article 42 and Article 43 Number 41 of 2004 concerning Waqf explains that Nadzir has an obligation to manage Waqf in Accordance with Sharia Principles.